The Role of Lecturers in Developing Digital-Based Adaptive Learning for Students - Pietra Dorand; Marlina Marlina; Abi Sofyan; Bernardus Agus Rukiyanto; Melvianus Selan (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid development of information and communication technology in recent decades has brought significant changes to various aspects of life, including higher education. This study aims to analyze the role of lecturers in developing digital-based adaptive learning for students in the era of technological transformation. The approach used in this study is qualitative with a descriptive research type. Data were collected through in-depth interviews, observations, and documentation of lecturers and students involved in the digital-based learning process. Data analysis techniques were carried out using an interactive model that includes data reduction, data presentation, and drawing conclusions, and its validity was tested through triangulation of sources and methods. The results of the study indicate that lecturers have a very important role as facilitators, motivators, and innovators in creating digital-based adaptive learning. Lecturers who are able to optimally utilize digital technology tend to be more successful in increasing student participation, motivation, and learning outcomes. However, this study also found various obstacles, such as limited digital competence, infrastructure, and lecturer readiness in managing adaptive learning. Therefore, institutional support is needed through training and the provision of adequate facilities. This research is expected to contribute to the development of more effective digital-based adaptive learning strategies in higher education.